Sao Tome and Principe : Review of Performance Under a Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews performance of Sao Tome and Principe under the Staff-Monitored Program (SMP). Sao Tome and Principe's Poverty Reduction and Growth Facility-supported program went off track at end-2000 because of fiscal and structural slippages, which were compounded in 2001 by the emergence of oil-sector governance concerns. The authorities requested an SMP for the first half of 2002, but spending overruns reoccurred, and most of the SMP's benchmarks were missed. Program implementation during the first half of 2002 was disappointing, as the key quantitative benchmarks for end-June 2002 were not observed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet